If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 42 = 26 Reorder the terms: 42 + x = 26 Solving 42 + x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + x = 26 + -42 Combine like terms: 42 + -42 = 0 0 + x = 26 + -42 x = 26 + -42 Combine like terms: 26 + -42 = -16 x = -16 Simplifying x = -16
| 88-2x=10x+16 | | (2x-9)(2x+7)=(2x-5)(2x+3) | | M-2=8 | | 6x(-9)= | | 8=x-(-1) | | 2x+26=9x-51 | | 2b+5=7 | | 12-8x=72-22x | | 3=r-14 | | -1-8x=10x+23 | | 223-6x=30x+23 | | 5x-26=34 | | 12x-33=7x+2 | | 3x+10=-67-8x | | 2(p-3)=4(p-10) | | 15v^2-19v-10= | | 114-10x=7x+22 | | 4x+10=82-4x | | 2y+5=9 | | 5x-25=20 | | 7+10=115+x | | 110-6x=3x+11 | | -16-5x=12-9x | | 4x+14=77-5x | | -2(5x-3)=-10x+11 | | 3x+25=12x-83 | | 3x+30=5x+14 | | 3x^2-4x+5=0 | | 3x-3=11x-43 | | 2x+29=12x-91 | | x^2-6=0 | | 5x-8=6x-1 |